BASIS DATA TERDISTRIBUSI UNTUK DATA INVENTARIS BARANG - Susan Dian Purnamasari; Eka Puji Agustini (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2016)
system can not be separated from the database. The database can either be petrified management in data processing in a rapid, precise and accurate . One of distributed database is one of 3 types of databases that can be used apart from the type of relational database, database integration. For a company that has many branches of the need for a database that can hold large amounts of data with very necessary , a distributed database is appropriate for the management of data bases that can be used in several branches of the company. This research will discuss a distributed database system for managing data inventory. So the data inventory at each branch can be distributed and reported quickly and efficiently.